A Study of the Effect of Resistance Training on Kidney Function in Female Rats Treated with Different Sex Hormones - Saleh, Khitam Hassan (American Journal of Biology and Natural Sciences, 2025)
The current research aims to study the efficacy of resistance training in protecting and maintaining kidney function in female rats treated with sex hormone therapy. The study sample consisted of a group of female rats classified into four groups based on the treatment method and the extent of resistance training. Some of these rats were injected with testosterone cypionate regularly, one injection every ten days, for a period of one and a half months. The changes that occurred in the study sample were detected through microscopic blood and urine examinations. The results showed that the training enhanced kidney cell resistance, reducing phagocytic cell proliferation and infiltration, and mitigating the risks of chemotherapy by improving kidney function.